Performance Evaluation of Capuchin Search Algorithm Through Non-linear Problems, and Optimization of Gear Train Design Problem - Eker, Erdal (Hibetullah KILIÇ, 2023)
[Abstract Not Available]
Keywords: Yazılım Mühendisliği (Diğer)